2020
DOI: 10.1016/j.ebiom.2020.102985
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol crystals use complement to increase NLRP3 signaling pathways in coronary and carotid atherosclerosis

Abstract: Background During atherogenesis, cholesterol precipitates into cholesterol crystals (CC) in the vessel wall, which trigger plaque inflammation by activating the NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome. We investigated the relationship between CC, complement and NLRP3 in patients with cardiovascular disease. Methods We analysed plasma, peripheral blood mononuclear cells (PBMC) and carotid plaques from patients with advanced atherosclerosis ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 41 publications
2
31
0
2
Order By: Relevance
“…The genes (CD33, CD53, CYBB, FCER1G, FPR2, LILRB2) enriched for immunity-related genes. In carotid plaques, C3aR1 26 and FCER1G 27 is higher compared to control arteries. CCR1 alters the immuno-inflammatory response in atherosclerosis.…”
Section: Discussionmentioning
confidence: 73%
“…The genes (CD33, CD53, CYBB, FCER1G, FPR2, LILRB2) enriched for immunity-related genes. In carotid plaques, C3aR1 26 and FCER1G 27 is higher compared to control arteries. CCR1 alters the immuno-inflammatory response in atherosclerosis.…”
Section: Discussionmentioning
confidence: 73%
“…Inflammation-induced by cholesterol crystals (CC) is the crucial step in the progression of CAS. CCs mediate complement activation and induce plaque inflammation by activating NACHT, LRR, and PYD domains harboring protein 3 (NLRP3) [ 25 ]. Elsewhere, Gregersen reported that plasma IL-27 levels in CAS patients were significantly higher than that of normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Complement C5a Receptor 1 (C5AR1) combines with complement C5a to recruit monocytes and neutrophils, which are involved in a variety of in ammatory disease processes. In patients with carotid artery plaque, C5a, C5AR1,and the release of IL-1β, IL-18 and IL-1α34 28 are signi cantly increased compared with healthy carotid artery tissue, indicating C5AR1 may be a promoter in progression of atherosclerosis.…”
Section: Ppi Network Analysismentioning
confidence: 98%